Studi Perbandingan: Adakah Dampak Event MotoGP Indonesia 2023 Terhadap Pergerakan Pasar Modal pada Entitas Bisnis Sektor Transportasi di BEI? - Indah Puspita Ganeswati; Damayanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study is an event-based study that aims to evaluate the impact of the 2023 Indonesian MotoGP championship on the response of the Indonesian capital market, with a focus on business entities in the transportation sector listed on the Indonesia Stock Exchange. The secondary data used in this study is sourced from the Indonesia Stock Exchange website and Yahoo Finance is used as information. The duration of the observation covers 10 days before (D-10) to 10 days after (D+10) MotoGP events. Paired sample t-test and wilcoxon signed rank test are applied in the analysis method. The findings of the study explained: 1) there was no relevant variation in returns before and after the Indonesian MotoGP event; 2) abnormal returns before and after the Indonesian MotoGP event did not indicate a significant difference; 3) differences in the level of trading volume activity before and after the Indonesian MotoGP event were found. This research provides important insights into the impact of events.